FACTORS THAT INFLUENCE THE FINTECH USERS IN CHOOSING DANA DIGITAL WALLET - Heny Kurnianingsih; Andreas Galih Saputro (Jurnal Revolusi Indonesia, 2021)
The rapid development of technology requires the mapping of technology, data, and communication revolution. One of industry that grew rapidly is mobile payments. The main attraction of m-payment is that consumers can buy and pay the products by using a smartphone only. DANA is one of the digital wallets that has a significant increase in users, where initially DANA was ranked in the top 10 to the top 3, after Ovo and Gojek. Aspects that affect the users of DANA digital wallet were measured from 4 variables that were promotion, accessibility, social, and emotional. The purpose of this study was to measure the influence of promotional, accessibility, social, and emotional aspects in determining the decision to use DANA. The study was a quantitative research, which the data collection used questionnaires that distributed online. The score was rated on a scale of 1-5. The subjects of the study were DANA users in Surakarta and surrounding areas, with sample of 100 people. The data were analyzed using SPSS software, including validity, reliability, linear regression test, T test, and F test. The results showed that the promotion aspect had a significance level of 0.020, accessibility 0.000, social 0.047, and emotional 0.071. It can be concluded that promotion, accessibility, and social aspects significantly influence the decision to use DANA, while the emotional aspect did not have a significant influence.